Responding to Problems in Dental Practice with Transparency and Accountability - Kerry R. Streiff; Thomas H. Gallagher; Julie Morath (Journal of the California Dental Association)
Background Few situations are as stressful for dentists as when a harmful error has occurred in their care of a patient. Embarrassment, fear of litigation, and uncertainty about what to say and how the patient will react can complicate the response. While most dentists are committed to responding to problems with transparency and accountability, turning these principles into practice can be difficult.Description In this article, we discuss the lessons that dentistry can learn from the field of Medicine about being more transparent with patients about care problems and aligning this transparency with broader efforts to promote a culture of safety where openness and accountability drive learning and improvement. Transparency is recognized as a precondition to a culture of safety, and has many elements including open communication with patients and families, colleagues, and organizations about problems. While fear of litigation is a frequent concern when clinicians are contemplating being open with a patient about something that went wrong, robust evidence suggests that transparency, when approached in a disciplined and thoughtful manner, can actually reduce the chances of lawsuits. Communication and Resolution Programs are structured processes that can support dentists in their response to problems in care. The Dental Patient Safety Foundation is another important resource all dentists should know about and partner with to improve their practice. We provide practical suggestions that dentists can apply to their practice now to reduce the chances of harm events happening and to be better prepared to respond effectively when harm events occur.